2021
DOI: 10.3390/ijerph18179128
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Overweight and Its Association with Mid-Upper Arm Circumference among Female and Male Farmers in Tanzania and Mozambique

Abstract: The increasing prevalence of overweight/obesity may already have reached the farmers in Tanzania and Mozambique. Here, the measurement of the mid-upper-arm-circumference (MUAC) could become a simple and sensitive tool for early detection of at-risk groups of overweight as well as underweight. Body Mass Index (BMI) and MUAC of female and male farmers (n = 2106) from different regions of Tanzania and the Zambézia province, Mozambique, were analyzed by region, sex, age, and correlates. MUAC cut-offs, calculated v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…Similarly, MUAC has good discriminatory ability with an AUC of 0.83 for overweight and obesity among females. These findings are supported by previous studies conducted in China, India, Japan, Tanzania and Mozambique, South Africa, and Juba which revealed that MUAC is an effective alternative tool to predict overweight or obesity among the adult population [ 34 , 35 , 47 , 49 , 50 , 51 ]. The study conducted in Japan stated that MUAC is a cheap and easily measurable tool to assess overweight or obesity than BMI [ 51 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, MUAC has good discriminatory ability with an AUC of 0.83 for overweight and obesity among females. These findings are supported by previous studies conducted in China, India, Japan, Tanzania and Mozambique, South Africa, and Juba which revealed that MUAC is an effective alternative tool to predict overweight or obesity among the adult population [ 34 , 35 , 47 , 49 , 50 , 51 ]. The study conducted in Japan stated that MUAC is a cheap and easily measurable tool to assess overweight or obesity than BMI [ 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our study revealed that MAUC has a strong positive correlation with BMI, which is indicative of MUAC screening capacity for overweight and obesity in adults. Previous similar studies affirmed that MUAC has a strong positive correlation with BMI [ 21 , 28 , 32 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. This strong positive correlation between MUAC and BMI suggests that these indices could give us comparable measurements while being utilized to assess the nutritional status of the adult population.…”
Section: Discussionmentioning
confidence: 75%
“…Body mass index (BMI) was calculated from weight and height measured at admission; cut-offs for underweight (<18.5 kg/m 2 ), overweight (≥25 kg/m 2 ) and obesity (≥30 kg/m 2 ) were used according to WHO and FANTA instructions [ 25 , 26 ]. MUAC cut-offs demonstrating underweight at <24 cm, overweight at ≥30 cm and obesity at ≥33.5 cm were set based on suggestions from recent studies [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Differences between individual groups were assessed by the Kruskal–Wallis and pairwise multiple comparison tests or the Chi Square test as appropriate (all p values are <0.001 for general group comparisons); values within a row not sharing a common superscript letter ( a,b,c,d ) are significantly different at p < 0.05. MUAC cut-off <24 cm for underweight [ 28 ], ≥30 cm for overweight and ≥33.5 cm for obesity [ 27 ]. Anemia is defined as hemoglobin <120 g/L for non-pregnant and <110 g/L for pregnant women and <130 g/L for men [ 29 ].…”
Section: Tablementioning
confidence: 99%
“…The simplicity of MUAC measurement means it does not require mathematical derivation [ 11 ], frontline professionals or expensive equipment compared to the requirements for measuring BMI [ 11 ]. MUAC is a practical tool for screening and grading the severity of nutritional status problems in the general population [ 12 , 13 ] and it has demonstrated superiority over BMI [ 6 ]. Moreover, previous studies have reported a positive correlation between MUAC and BMI [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%